Colossal Granular Lithium Deposits Enabled by the Grain‐Coarsening Effect for High‐Efficiency Lithium Metal Full Batteries. Issue 24 (11th May 2020) - Zhang, Weidong; Wu, Qiang; Huang, Jinxin; Fan, Lei; Shen, Zeyu; He, Yi; Feng, Qi; Zhu, Guannan; Lu, Yingying
Abstract: The low Coulombic efficiency of the lithium metal anode is recognized as the real bottleneck to practical high‐efficiency lithium metal batteries with limited Li excess. The grain size and microstructure of deposited lithium strongly influences the lithium plating/stripping efficiency. Here, a solubilizer‐mediated carbonate electrolyte that can realize grain coarsening of lithium deposits (>20 µm in width) with oriented columnar morphology, which is in sharp contrast with conventional nanoscale dendrite‐like lithium deposits in carbonate electrolytes, is reported. It exhibits improved Li Coulombic efficiency to 98.14% at a high capacity of 3 mAh cm −2 over 150 cycles, because the colossal lithium deposition with minimal tortuosity can maintain the bulk Li with continuous electron conducting pathway during the stripping process, thus enabling efficient Li utilization. Li/NMC811 full batteries, composed of thin Li anode (45 µm) and a high‐capacity NMC811 cathode (16.7 mg cm −2 ), can achieve at least 12 times longer lifespan (200 cycles). Abstract : A grain‐coarsening behavior of lithium deposits with oriented columnar morphology can be realized in a solubilizer‐mediated carbonate electrolyte. Nanowave‐structured solid electrolyte interphases derived from the Sn 2+ –NO3 – coordination‐solvation structure promote a significant improvement in the lifespan (200 cycles) of Li/NMC811 full batteries (45 µm thin Li anode and 16.7 mg cm −2 NMC811 cathode).